2021
DOI: 10.3389/fvets.2021.782409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Enhancer Map of Cattle Muscle Genome Annotated by ATAC-Seq

Abstract: Annotating regulatory elements could benefit the interpretation of the molecular mechanism of genome-wide association study (GWAS) hits. In this work, we performed transposase-accessible chromatin with sequencing (ATAC-seq) to annotate the cattle muscle genome's functional elements. A total of 10,023 and 11,360 peaks were revealed in muscle genomes of adult and embryo cattle, respectively. The two peak sets produced 8,850 differentially accessible regions (DARs), including 2,515 promoters and 4,319 putative en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The ENCODE guidelines for ATAC-seq projects recommend 50 million reads for paired-end sequencing for each replicate ( , accessed on 6 September 2021). Recent studies in cattle identified accessible chromatin regions in different tissues, including muscle, bronchial lymph nodes, liver, lung, hypothalamus, brain, adipose, and spleen [ 12 , 13 , 14 , 39 ]; however, none of them evaluated rumen tissue. This study aimed to identify accessible chromatin regions and genomic regulatory elements that may control rumen epithelial development changes during weaning in calves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ENCODE guidelines for ATAC-seq projects recommend 50 million reads for paired-end sequencing for each replicate ( , accessed on 6 September 2021). Recent studies in cattle identified accessible chromatin regions in different tissues, including muscle, bronchial lymph nodes, liver, lung, hypothalamus, brain, adipose, and spleen [ 12 , 13 , 14 , 39 ]; however, none of them evaluated rumen tissue. This study aimed to identify accessible chromatin regions and genomic regulatory elements that may control rumen epithelial development changes during weaning in calves.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ATAC-seq for rumen epithelial tissue to generate a comprehensive landscape of chromatin events will advance our knowledge of the regulatory element mechanisms in play during rumen development. Few studies have used ATAC-seq in cattle [ 12 , 13 , 14 ]. Recent studies using ATAC-seq reported open chromatin regions for bronchial lymph nodes of dairy calves [ 12 ]; liver, muscle, and hypothalamus of indicine cattle [ 13 ]; and muscle tissue in adults and embryos from Qinchuan cattle [ 14 ]; however, none of them evaluated rumen, especially in the critical weaning period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, particularly in bovine models, previous studies in the context of skeletal muscle chromatin accessibility have mainly focused on comparative analysis across distant species to identify tissue‐specific regulatory elements 20–22 . Recently, Cao et al described comparative analysis of enhancers between adult and embryo bovine muscle using chromatin accessibility 23 . Despite the foetal stage is critical for skeletal muscle development, only limited evidence of foetal muscle growth and development was available from prior studies, and these findings may ignore that skeletal muscle development is a dynamic process comprised of multiple developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Recently, Cao et al described comparative analysis of enhancers between adult and embryo bovine muscle using chromatin accessibility. 23 Despite the foetal stage is critical for skeletal muscle development, only limited evidence of foetal muscle growth and development was available from prior studies, and these findings may ignore that skeletal muscle development is a dynamic process comprised of multiple developmental stages. In our study, we reconstructed the course of myogenic differentiation in vitro, providing an ideal model to define when and how these regulatory changes occur during skeletal muscle development.…”
mentioning
confidence: 99%